Pronunciation Error Done by Some Indonesian Prominent Public Figures on YouTube Channel - Rafi’i, Muhammad (Institut Agama Islam Negeri Palopo, 2024)
This article examines pronunciation errors made by several prominent public figures in Indonesia on YouTube. Many Indonesians hold the belief that since they live in Indonesia, proper pronunciation is not a priority. Unfortunately, this leads to a lack of awareness about the importance of correct pronunciation and spelling. Often, learners focus on grammar and vocabulary acquisition when learning a foreign language, while neglecting pronunciation. As a result, most English learners excel in listening and reading, but struggle with speaking accurately.The study aims to explore the variations in English pronunciation by well-known individuals in Indonesia, specifically Prabowo Subianto, Prilly Latuconsina, and Cania Citta. The objectives are to identify common issues with English vowel and consonant pronunciation and to uncover the reasons behind these errors. The subjects of the study were Prabowo Subianto, Prilly Latuconsina, and Cania Citta. The researcher carefully watched YouTube videos featuring these individuals, analyzed their speech, and produced phonetic transcriptions. Error analysis was employed to evaluate the data, focusing on three areas: transcription of the subjects' pronunciation, difficulties with short vowels, and difficulties with long vowels.